'Tell Me the Landscapes in Which You Live and I Will Tell You Who You Are' – Online Theology Students Crossing Thresholds in Religious Education and Spirituality Against an Australian Desert Context. Issue 2 (2nd July 2016) - Mudge, Peter
Abstract : This article proposes that in the crossing of learning thresholds, it is possible to identify a number of significant intersections between three key areas – (1) stories about teaching challenges provided by an initial survey of 60 selected online adults studying religious education (RE), spirituality and theology; (2) the crossing of the Australian bush, frontier, or desert landscape; and (3) threshold concept (TC) theory. This survey of online teacher views revealed five specific teacher learning challenges that could be compared with five selected features of the Australian bush or desert landscape. Narratives of teacher learning challenges were extracted from a range of online discussion scripts, while certain features of the Australian landscape emerged from a later, unplanned literature analysis of that topic. This article examines two of these thematic clusters, related to liminality and to 'stretching' of teachers, in relation to desert literature and TC theory. The article closes with a series of conclusions and discussion points emerging from the research.